Studi Pemilihan Moda Transportasi Antara Angkutan Umum Dalam Trayek dan Angkutan Sewa Khusus di Kota Tarakan - Muhammad Djaya Bakri; Nila Riani; Iif Ahmad Syarif (Borneo Engineering : Jurnal Teknik Sipil, 2023)
The development of technology, there are now various modes of transportation that serve the community such as public transportation on routes and special rental transportation (online). The operation of online-based special rental transportation in Tarakan City lately has had the impact of decreasing customer interest in using public transportation to support their movements. This phenomenon is interesting to do research to find out the best type of public transport and variables that are very influential in the selection of public transport by travelers in Tarakan City. This public transport selection research was analyzed using the Analytical Hierarchy Process method, with research attributes including: cost, safety, comfort, ease of getting the mode, travel time, and service. Primary data was obtained through interviews/questionnaires to respondents selected by simple random sampling method, with a total of 100 people as a representation of the population of Tarakan city in 2021. The results of the analysis show that the public transport mode chosen by customers based on the specified criteria is Special Rental Transport with an average value of 5.965 compared to Public Transport in Tracks (5.711). The influential criteria for customers in choosing public transportation is the cost criteria with a weight value of 36.479, followed by the criteria for ease of getting the mode (14.591), security (12.906), service (12.706), comfort (12.177), and service time criteria with a value of 11.16.